Coastal gravity field refinement by combining airborne and ground-based data - Wu, Y.; Abulaitijiang, A.; Featherstone, Will; McCubbine, J.C.; Andersen, O.B. (SPRINGER, 2019)
© 2019, Springer-Verlag GmbH Germany, part of Springer Nature.